Creative Writing as an Effort to Improve Children's Emotional Intelligence - Encil Puspitoningrum; Rosa Imani Khan; Daniel Swanjaya (Qubahan Academic Journal)
Emotional intelligence is an essential ability for every individual from an early age. This study explores the potential of creative writing as an alternative method in improving children's emotional intelligence. Through creative writing activities, children are expected to express their emotions and feelings more openly and develop empathy and self-recognition skills. This research utilizes a qualitative method. Data was collected through a literature review of similar studies. The results showed that creative writing was effective in helping children identify and manage their emotions better. In addition, this activity also improves children's ability to understand others' perspectives and develop critical social skills. This research provides new insights into the potential of creative writing to develop children's emotional intelligence and its implications in education and parenting.